CFD-Based Design of Focal Brain Cooling System for Suppressing Epileptic Seizures - Hata, Kei; Abe, Takuto; Inoue, Takao; Fujiwara, Koichi; Kubo, Takatomi; Yamakawa, Toshitaka; Nomura, Sadahiro; Imoto, Hirochika; Suzuki, Michiyasu; Kano, Manabu (Computer Aided Chemical Engineering, 2018)
Epilepsy is a group of neurological disorders which is caused by excessive neuronal activities in cerebrum and characterized by recurrent seizures. A quarter of patients have intractable epilepsy and do not become seizure-free with medication. We are developing an implantable and wearable focal brain cooling system, which enables the patients to lead ordinary daily life. The system cools the epileptic focus, where the excessive neuronal activities begin, by delivering cold saline to a cranially implanted cooling device. In this research, we developed a whole system model through the first principles and animal experiments. The results of system design have shown that a cooling device with more complex channel structure achieves higher temperature uniformity in the brain with lower flow rate of saline. The optimal structure was derived by taking account of the trade-off between pressure drop and temperature uniformity. In addition, the results have demonstrated that the cooling duration is less than 10 minutes for the average temperature 2mm below the cooling device (inside the brain) to reach 25 °C; it is short enough to cool the brain after seizure is predicted by existing electroencephalogram (EEG)-based algorithms. Moreover, the frequency of battery charging would be once in several days for most patients.